GROWTH PERFORMANCE AND SERUM BIOCHEMICAL PROFILE IN YANKASA RAMS FED ALKALI-TREATED GROUNDNUT SHELLS - Millam, Jacob; Bello, S. S.; Abbaya, H. Y.; John, P. A. (FUDMA JOURNAL OF SCIENCES, 2020)
The study was conducted to assess the chemical composition of alkali treated groundnut shells and their effects on growth and serum biochemical parameters in Yankasa rams. A total of 4 Yankasa rams where used to conduct the experiment in a 4Ã—4 Latin square design. Four diets (14% crude protein) were formulated to contain untreated groundnut shell (UTGNS), urea treated groundnut shell (UGNS), lime treated groundnut shell (LGNS) and urea-lime treated groundnut shell (ULGNS). Growth and blood serum parameters were measured at the end of each period. Samples of the treated groundnut shell and the experimental diets were analysed for proximate analysis, neutral detergent fibre, acid detergent fibre and lignin. The results of the chemical composition of treated groundnut shell showed that alkali chemical increased the protein, energy, and reduced the cell wall constituents of the untreated groundnut shell. Significant (P
Keywords: Urea, lime, groundnut shell, feed intake, weight gain, feed conversion ratio, serum indices, and Yankasa rams